2011
DOI: 10.2166/wst.2011.245
|View full text |Cite
|
Sign up to set email alerts
|

Removal of ammonium from rare-earth wastewater using natural brucite as a magnesium source of struvite precipitation

Abstract: This paper presents a study regarding ammonium removal from rare-earth wastewater by struvite precipitation with natural brucite mineral as a source of magnesium. Experimental results indicated that a pH ranging from 8.5 to 9.5 was the optimum for the removal of ammonium using the soluble form of brucite as a magnesium source. Additionally, when solid brucite was used as a magnesium source as well as an alkali reagent, the initial ammonium concentration of 4,535 mg/L decreased to 239-317 mg/L after an reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 20 publications
(22 reference statements)
1
15
0
Order By: Relevance
“…It is helpful in recycling of vital nutrients. Different studies suggested that among different agro-waste, cattle manure is very successful in recovery of struvite [113,114], followed by swine manure [108,109,115,116], poultry manure [117], and lastly cattle urine [118]. Generally, farm wastes containing manures are abundant in P and NH 4 + , which is advantageous for struvite recovery.…”
Section: Phosphorus Recoverymentioning
confidence: 99%
“…It is helpful in recycling of vital nutrients. Different studies suggested that among different agro-waste, cattle manure is very successful in recovery of struvite [113,114], followed by swine manure [108,109,115,116], poultry manure [117], and lastly cattle urine [118]. Generally, farm wastes containing manures are abundant in P and NH 4 + , which is advantageous for struvite recovery.…”
Section: Phosphorus Recoverymentioning
confidence: 99%
“…Due to the relatively high price of these commercial salts, and since magnesium is listed in the European Union's critical raw material list, alternative magnesium sources should be preferred instead of commercial salts [13]. For these reasons, several authors have studied various inexpensive Mg-sources for struvite precipitation, including brucite [14], seawater [12,15], magnesite [16], bottom and fly ash [17,18], dolomite (DOL) [19,20], and MgO-saponification wastewater [21].…”
Section: Introductionmentioning
confidence: 99%
“…Commonly used precipitants for struvite precipitation are MgCl 2 , MgSO 4 MgO, and Mg(OH) 2 [29,30], but due to the high price of these commercial salts, and since magnesium is listed in European Union's critical raw material list, alternative magnesium containing side streams and industrial waste material should be preferred instead of magnesium salts [1,31]. Therefore, inexpensive magnesium sources such as magnesite [32], brucite [33], a by-product of marine salt manufacturing and by-product of the thermal treatment of meat waste, bone meal, etc. [34], MgO-saponification wastewater [35], seawater [36,37], and bottom ash collected from a small residential fireplace [38] to produce struvite have been tested in several papers.…”
Section: Introductionmentioning
confidence: 99%